The Anti-allergic Cromones: Past, Present, and Future - Sinniah, Ajantha; Yazid, Samia; Flower, Roderick J. (Frontiers in Pharmacology, 2017)
The anti-allergic cromones were originally synthesised in the 1960s by Fisons Plc, and the original drug emerging from this program, disodium cromoglycate was subsequently marketed for the treatment of asthma and other allergic conditions. Whilst early studies demonstrated that the ability of the cromones to prevent allergic reactions was due to their ‘mast cell stabilising’ properties, the exact pharmacological mechanism by which this occurred, remained a mystery. Here, we briefly review the history of these drugs, recount some aspects of their pharmacology and discuss two new explanations for their unique actions. We further suggest how these findings could be used to predict further uses for the cromones.